SUITABILITY ASSESSMENT AND STORAGE CAPACITY ESTIMATES OF RAMBUTAN COAL SEAMS FOR CO2 STORAGE - Utomo Pratama Iskandar (Scientific Contributions Oil and Gas, 2013)
Coal seams are an alternative storage options besides depleted oil and gas reservoirs and deep salineformations. They are suitable to different degrees for CO2 geological storage as a result of various intrinsicand extrinsic. The potential use of this geological media requires suitability assessment and the amountof CO2 can be stored. This paper presents the fi rst attempt to evaluate the characteristics of coal seams inRambutan Field, South Sumatera, in terms of their suitability for CO2 storage and the potential storagecapacity. A set of 5 semi-qualitative criteria has been developed for the assessment of 4 seams that includespermeability, coal geometry, structure, homogeneity and depth. CO2 adsorption capacity estimates werederived from laboratory experiment by employing Isothermal Langmuir. The results show the 4 seams ingeneral are suitable for CO2 storage. The adsorption capacity from seam 2, 3, 5 and P are 22.18, 25.09,24.53, and 34.12 m3/t dry-ash-free basis respectively. The highest CO2 storage capacity can be stored atseam P enabling the CO2 in dense phase (supercritical).